Zeolites and adsorption: model materials and applications. - Thommes, Matthias; et al. (Zeolites, 2008)
A review. During the past decades gas adsorption techniques have grown into a key sepn. tool in industry. Such expansion of adsorption processes resulted from a series of significant scientific and engineering developments, including invention of synthetic zeolites and tech. advancement or optimization of adsorption process, such as PSA (pressure swing adsorption). As the aforementioned fields in adsorption science and technol. are well represented in the available literature, herein we restrict the discussion to selected, most important sepn. processes based on zeolite materials. Since the textural characterization of zeolites is crucial for their applications, detailed aspects of textural anal. by gas adsorption are discussed in the first part of this chapter. In the second part, important applications of zeolites in tech. adsorption processes are explained based on practical examples: (i) air sepn. into N2 and O2, (ii) drying of gases such as natural gases or compressed air, and hydrogen purifn. [on SciFinder(R)]
Keywords: review zeolite adsorption sepn